Emerging drugs for Waldenström's macroglobulinemia - Kastritis, E.; Terpos, E.; Dimopoulos, M.A. (Expert Opinion on Emerging Drugs, 2011)
Introduction: Waldenström's macroglobulinemia (WM) is a rare but distinct B-cell lymphoproliferative disorder characterized by lymphoplasmacytic bone marrow infiltration and IgM monoclonal paraproteinemia. Alkylators or nucleosides analogs, often in combination with rituximab, are the most commonly used drugs, but WM will relapse and even salvage treatments may fail. Areas covered: We present recent advances on the treatment of WM, focusing on drugs that are under clinical investigation and for which data indicate promising activity and positive future prospects. Bortezomib is a proteasome inhibitor that eventually becomes a major treatment option for WM. Everolimus and perifosine which target mTOR (mammalian target of rapamycin) and Akt, respectively, of the PI3K/AKT/mTOR pathway showed some activity. Bendamustine, a novel alkylating agent is active, especially in combination with rituximab. Immunomodulatory drugs can act synergistically with rituximab but are toxic. Targeting surface antigens of the lymphoplasmatic cells have shown promising results. Expert opinion: Combinations of novel drugs with established agents are feasible and increase response rates but whether there will be an increase in the survival of patients with WM needs further investigation. The toxicity profile is an important determinant for the feasibility of these drugs in patients with WM. © 2011 Informa UK, Ltd.
Keywords: bendamustine; bortezomib; everolimus; lenalidomi D.E.; perifosine; Thalidomide